The role of attachment in adulthood: Is there a reason for pessimism or optimism? - Kamenov, Željka (2007)
Although the attachment theory emerged as an explanation of the emotional relationship between a child and a caregiver, Bowlby (1969) thought that the same attachment style system exists and functions throughout the individual’ s lifetime. Attached behavior becomes organized within one’ s self as an internal working model that defines emotional relationships during one’ s life. Based on the attachment theory, it can be concluded that the type of attachment once adopted in childhood structures the quality of relationships in adolescence and adult life. Therefore, the theory of attachment offers a promising theoretical framework for understanding friendship, marriage, romantic and other human relationships. Based on these ideas, several authors continued in the 1980’ s research in the field of adult attachment. Hazan and Shaver (1987), conceptualized romantic love, or pair bonding, as an attachment process that is characterized by dynamics similar to infant-parent attachment. Unlike Hazan and Shaver, whose starting point was the work of Ainsworth et al. (1978), Bartholomew (1990) starts from the Bowlby's theory framework, in which individuals internalize their experiences with caregivers, resulting in two notions which serve as the so-called working models: self model and model of others. These two dimensions provide the basis from which four attachment styles spring, depending on whether the individual has a positive or a negative model of self and others. Over the past two decades, there has been an explosion of research extending Bowlby’ s and Ainsworth’ s work on attachment in infancy to a broader theory of human functioning. The body of literature on adult attachment styles strongly supports the importance of secure attachments for well-being and interpersonal functioning. The benefits of the attachment security for adults are so widespread that Mikulincer and Florian (1998) consider it a general resilience factor across the life span. Attachment theory is a relatively deterministic theory of human psycho-social functioning. Bowlby’ s emphasis on the continuity of early attachment patterns into adulthood suggests that the attachment style developed with primary caretakers have a significant degree of stability over time and across relationships. However, some authors emphasize the data that have shown a substantial degree of no-overlap between the attachment style in infancy and adulthood, or respectable within-person variability in attachments to different attachment figures. From this perspective, attachment may be a transactional process. This revisionist perspective allows the possibility that not only could a person’ s attachment vary over time, but also that people could have different attachment styles with different relationship partners or significant others. In this article I present some of our studies and findings on adult attachment, which can roughly be divided in three lines of research: (1) consistency of the adult attachment style across different types of close relationships, (2) attachment and personality, and (3) romantic partners’ attachment styles compatibility. The data from our research, which show the intra-personal variation in the attachment to different attachment figures in various types of close relationships, support the revisionist perspective on attachment. We find it optimistic – it gives hope to all the people who have had any kind of unfortunate attachment history that things could change and that they could improve their interpersonal functioning and their overall well-being as all the others more fortunate ones.
Projekt MZOS
Projekt MZOS
ENG